35 рассказов "Литературной России" - Стефанович Юрий Анатольевич (Современник, 1984)
Экземпляры: Селтинская районная библиотека (к/х) (20220826) / Инвентарный номер: 88237 / Авт.знак: Т 67 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)6